NEEDS ANALYSIS AND COURSE DESIGN - Djoko Srijono (Universitas Muhammadiyah Surakarta, 2006)
Identifying learner needs is essential in English course design. Needs Analysis or Needs Assessment refers to an array of procedures for identifying and validating the learner needs and establishing priorities among them. Learner needs can b categorized into learning needs and target needs. Target needs comprise necessi- ties, lacks , and wants. Course designer uses a number of ways such as question- naire, interview, observation, and the like to collect information about learner needs. Needs Analysis has two categorizes of purposes; first, it is related to course design or curriculum development, and second, it is concerned with language teaching. Key words: Needs Analysis, Target Needs, Course Design, and Course Design Pro- cess.